Structure and dynamics of dense colloidal ellipsoids at the nearest-neighbor length scale - Antara Pal; Md. Arif Kamal; Peter Holmqvist; Peter Schurtenberger (Physical Review Research, 2021)
Anisotropic particles are known to exhibit a richer and more complex phase behavior in comparison to their spherical counterpart. While the majority of the existing studies address structural properties, the dynamic behavior of anisotropic particles is a relatively lesser explored avenue. Using multispeckle ultra-small-angle x-ray photon correlation spectroscopy (USA-XPCS), we have carried out a systematic investigation of the structural and dynamic properties of colloidal ellipsoids at the nearest-neighbor length scale. The USA-XPCS measurements have allowed us to probe, as a function of the volume fraction, the q-dependent effective structure factor, S_{eff}(q), along with the effective long time diffusion coefficient, D_{eff}(q), for this anisotropic system. Our results indicate a scaling behavior of D_{eff}(q) with 1/S_{eff}(q) from which we have estimated the effective amplitude function A_{eff}(q), which can be directly related to the effective hydrodynamic function H_{eff}(q). A_{eff}(q) shows a similar q dependence to that of S(q). Our investigation also allows for the precise determination of the volume fraction corresponding to the arrest transition.